Linking Pre-existing Metacognition Practices and Students’ Performance in High School Physics - Diate, Kim; Benasing, Rayyanah R.; Tee-Pastidio, Krystine Mae R. (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This research aims to provide insight on how student’s pre-existing metacognitive strategies influences their academic performance, specifically in learning physics.Methodology: This research administered the Physics Metacognition Inventory (PMI) scale to 117 Grade 9 students of the laboratory high school of MSU-Iligan Institute of Technology. PMI scale has an internal consistency of 0.90, indicating high-reliability of the instrument in measuring the constructs it intends to measure. Shapiro-Wilk’s test for normality reveals non-normal distribution (p-values < 0.05) , thus a non-parametric test (i.e., spearman rank correlation) is utilized to establish statistical correlation among the variables of interest (i.e, level of proficiency and factors on Physics Metacognition Inventory). Statistical analysis is done using RStudio Version 2023.06.0+421 (2023.06.0+421).Main Findings: Results suggest that student’s knowledge of cognition exhibits a strong positive correlation with their physics academic performance. Moreover, all five components of regulation of cognition showed positive correlation with the level of physics performance. However, the strongest predictor is the dimension of evaluation.Novelty/Originality of this study: This research highlights the role of pre-existing metacognitive strategies and how it is correlated to academic performance in a physics classroom. Understanding how each of the dimensions of metacognition correlates to physics performance can have an important implications on how physics instruction might be productively given to junior high school students especially with the goal of honing critical evaluation of one’s thinking, conceptual conclusions, and physical sensibility of solutions.